2023
DOI: 10.1002/mco2.238
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous vaccination with subunit protein vaccine induces a superior neutralizing capacity against BA.4/5‐included SARS‐CoV‐2 variants than homologous vaccination of mRNA vaccine

Abstract: BA.4 and BA.5 (BA.4/5), the subvariants of Omicron, are more transmissible than BA.1 with more robust immune evasion capability because of its unique spike protein mutations. In light of such situation, the vaccination against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is in desperate need of the third booster. It has been reported that heterologous boosters might produce more effective immunity against wild‐type SARS‐CoV‐2 and the variants. Additionally, the third heterologous protein subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(84 reference statements)
1
4
0
Order By: Relevance
“…This approach is similarly to a recent report on intranasal S protein booster after primary mRNA vaccination, which also induced IgA production at the respiratory mucosa, boosted systemic immunity, and elicited more broadly neutralizing antibodies against sarbecoviruses (46). The heterologous mRNA priming and subunit protein booster immunizations were shown to increase the breadth of neutralizing antibodies against the SARS-CoV-2 variants in mice (23) and non-human primates (47). Although further investigation is needed to determine whether the RBD-LTA fusion proteins can provide effective transmission-blocking, the current findings can provide the information for developing a mucosal booster COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This approach is similarly to a recent report on intranasal S protein booster after primary mRNA vaccination, which also induced IgA production at the respiratory mucosa, boosted systemic immunity, and elicited more broadly neutralizing antibodies against sarbecoviruses (46). The heterologous mRNA priming and subunit protein booster immunizations were shown to increase the breadth of neutralizing antibodies against the SARS-CoV-2 variants in mice (23) and non-human primates (47). Although further investigation is needed to determine whether the RBD-LTA fusion proteins can provide effective transmission-blocking, the current findings can provide the information for developing a mucosal booster COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous RBD-based COVID-19 vaccines have been developed, including those using different expression platforms and adjuvant systems (13)(14)(15)(16)(17)(18)(19)(20)(21). Recent improvements to the RBDbased vaccine approach include the use of RBD dimer of delta and omicron (22), heterologous priming with mRNA vaccines (23), and STING-based adjuvants (24) to generate neutralizing antibodies against the immune evasive Omicron BQ and XBB subvariants (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were intramuscularly immunized with an mRNA vaccine (0.1 μg or 1 μg per mouse) encoding Delta full-length SARS-CoV-2 S protein, 16 followed by intranasal immunization with 10 μg RBD-HR vaccine containing Delta-derived self-assembled trimeric protein 17 ( Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…6–8 weeks female NIH mice (Charles River Laboratory) were randomly divided into different groups and housed in the Animal Center at the School of Public Health (Sichuan University, Chengdu, China) under specific pathogen-free conditions at room temperature (24 ± 2 °C) and constant humidity (55% ± 10%) on a 12 h–12 h light–dark cycle. Regarding immunization, the groups of mice ( n = 6) first received two doses of the mRNA vaccine (0.1 μg or 1 μg per mouse) intramuscularly, 16 followed by two doses of the RBD-HR protein vaccine 17 (10 μg per mouse) administered intranasally with a 21-day interval between each dose ( Fig. 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…This implied that a heterologous mRNA/protein boost regimen is more efficient to induce humoral immune responses than the homologous mRNA/mRNA vaccine. Furthermore, several studies showed not only an enhanced and more sustained SARS-CoV-2 S-but also influenza hemagglutinin (HA)-specific antibody response in old individuals induced through heterologous mRNA-prime/protein-boost regimens as compared to homologous mRNA vaccination (80)(81)(82)(83). Interestingly, there was also increasing evidence that different antigen-specific heterologous prime/boost strategies might also improve the efficacy of currently available vaccines.…”
Section: Discussionmentioning
confidence: 99%